Can routine screening for alcohol consumption in pregnancy be ethically and legally justified? - Bennett, Rebecca (Journal of medical ethics, 2022)
In the UK, it has been proposed that alongside the current advice to abstain from alcohol completely in pregnancy, there should be increased screening of pregnant women for alcohol consumption in order to prevent instances of fetal alcohol spectrum disorder. The Scottish Intercollegiate Guidelines Network published guidelines in 2019 recommending that standardised screening questionnaires and associated use of biomarkers should be considered to identify alcohol exposure in pregnancy. This was followed in 2020 by the National Institute for Health and Care Excellence Draft Quality Standard, which recommended that pregnant women should have information on their alcohol consumption recorded throughout their pregnancy and this information transferred to the child’s health records. Most recently, Public Health England has stated that the alcohol intake of all women should be recorded throughout pregnancy, not just at the initial booking appointment and that tools such as blood biomarkers and meconium testing should be researched in order to determine true prevalence rates of alcohol in pregnancy. We argue that this proposed enhanced screening undermines women’s autonomy and their legal right to be sufficiently informed to consent to screening. We argue that there is no evidence that this kind of screening will result in a reduction of fetal harm and there is a danger that undermining the autonomy of women and the trust relationship between women and healthcare professionals may even increase harm to future children.